Draft Annual Plan (2008-2009) Administration of Union Territory of Dadra and Nagar Haveli - Planning Commission (Planning Commission, 2008)
The Union Territory of Dadra and Nagar Haveli is situated on the Western Coast of India between the parallels of 20° -0° and 20° -25° of latitude north and between the meridian 72° -50° and 73° -15° of longitude east. Its population as per 2001 Census is 2,20,490 (1,21,666 male and 98,824 females). It has an area of 491 sq.km, and comprises two enclaves viz. (1) Dadra and (2) Nagar Haveli, having 72 villages. Silvassa, the capital of this U.T. and its adjoining village Amli have been treated as non-statutory Census Town. The territory is surrounded by Valsad District of Gujarat and Thana District of Maharashtra.
Union Territory of Dadra and Nagar Haveli, Department of Planning and Statistics